APPROXIMATION BY N ÓRLUND TYPE MEANS IN THE GRAND LEBESGUE SPACES WITH VARIABLE EXPONENT - Jafarov, S. Z. (Udmurt State Univ, 2024)
In the present paper the approximation of functions by Norlund type means in the generalized grand Lebesgue spaces with variable exponent is studied.
Keywords: grand variable exponent Lebesgue spaces; modulus of smoothness; Lipschitz classes; trigonometric approximation; Norlund means